Fertility Preservation for Child and Adolescent Cancer Patients in Asian Countries - Takae, Seido; Lee, Jung Ryeol; Mahajan, Nalini; Wiweko, Budi; Sukcharoen, Nares; Novero, Virgilio; Anazodo, Antoinette Catherine; Gook, Debra; Tzeng, Chii-Ruey; Doo, Alexander Kenneth; Li, Wen; Le, Chau Thi Minh; et al. (Frontiers in Endocrinology, 2019)
Background: At present, fertility is one of the main concerns of young cancer patients. Following this trend, “fertility preservation (FP)” has been established and has become a new field of reproductive medicine. However, FP for child and adolescent (C-A) cancer patients is still developing, even in advanced countries. The aim of the present study was to assess the barriers to FP for C-A patients by investigating the current status of FP for C-A patients in Asian countries, which just have started FP activities. Method: A questionnaire survey of founding members of the Asian Society for Fertility Preservation (ASFP) was conducted in November 2018. Main findings: Of the 14 countries, 11 country representatives replied to this survey. FP for C-A patients is still developing in Asian countries, even in Australia, Japan, and Korea, which have organizations or academic societies specialized for FP. In all countries that replied to the present survey, the patients can receive embryo cryopreservation (EC), oocyte cryopreservation (OC), and sperm cryopreservation (SC) as FP. Compared with ovarian tissue cryopreservation (OTC), testicular tissue cryopreservation (TTC) is an uncommon FP treatment because of its still extremely experimental status (7 of 11 countries provide it). Most Asian countries can provide FP for C-A patients in terms of medical technology, but most lack sufficient experience and an established system due to barriers that inhibit promoting FP for C-A patients. “How to provide FP treatment for C-A” is a major barrier. Also, low recognition in society and among medical staff is still a particularly major issue. There is also a problem with cooperative systems with pediatric departments. To achieve high-quality FP for C-A patients, a multidisciplinary approach is vital, but, according to the present study, few paramedical staff can participate in FP for C-A patients in Asia. Only Australia and Korea) provide FP information by video and specific resources. Conclusion: The present study demonstrated the developing status of FP for C-A patients in Asian countries. More intensive consideration and discussion are needed to provide FP in Asian societies based on the local cultural and religious needs of patients.